Factors of Leadership and Organizational Behavior on the Accreditation of Schools in Tomohon City - R. Walukow, Maria; A.M Rawis, Joulanda; Tambingon, Henny N.; Kambey, Joseph (International Journal of Educational Research & Social Sciences, 2023)
Schools are declared accredited or not accredited based on the results of verification, clarification and validation, which are now summarized in the variables of the school accreditation instrument concerning the quality of graduates, the learning process, teacher performance and school management. This study describes school accreditation as a policy of education in Indonesia by examining leadership factors and organizational behavior towards current problems faced by the world of education, specifically high schools in Tomohon City. This paper is the result of a descriptive study using qualitative methods. The techniques used in the forms of literature study, observation, and interviews. Observations and interviews were carried out by researchers directly to high school level schools in Tomohon City. Based on the research results, all high schools in the city of Tomohon are accredited with the mechanism due to school leadership factors and the coordination of the Education Office Development Supervisors. On the other hand, schools that have expired accreditation status are caused by the lack of attention from school leaders and organizational behavior that is not functional.